Предпринимательский потенциал в контексте эволюции теории предпринимательства - Краснокутская, Наталия Станиславовна; Бубенец, Ирина Георгиевна (Видавничий дім "ІНЖЕК", 2014)
Цель статьи состоит в исследовании эволюции теории предпринимательства, этапизации этого процесса с выделением тех изменений, которые произошли в понимании характерных особенностей и предназначения предпринимателя и предпринимательского потенциала. Анализируя, систематизируя и обобщая научные труды многих ученых, была рассмотрена эволюция теории предпринимательства, систематизированы взгляды исследователей и определены характерные черты предпринимателя. В результате проведенного исследования выделены этапы эволюции теории предпринимательства. Определены отличительные особенности предпринимателя как носителя предпринимательского потенциала в контексте эволюции теории предпринимательства. Обосновано, что понимание содержания предпринимательского потенциала определяется возможностями создавать ценностное предложение, обусловленными наличием ресурсов, способностей и компетенций. Придерживаясь выделенных положений о зависимости характерных признаков предпринимательского потенциала от особенностей развития не только теории предпринимательства, но и национальных экономик, перспективы дальнейших исследований состоят в определении отличительных черт, присущих предпринимателям в условиях украинских реалий.

The purpose of this article is to study the evolution of the theory of entrepreneurship, to show the stages of this process with revealing of the changes that have occurred in the understanding of the characteristics and purpose of the entrepreneur and entrepreneurial capacity. Analyzing, systematizing and summarizing the scientific work of many scientists, the evolution of the theory of entrepreneurship was considered, the views of researchers and identified the characteristics of an entrepreneur were systematized. The study highlighted the stages of evolution of the theory of entrepreneurship. It defined the features of the entrepreneur as the bearer of the entrepreneurial potential in the context of the evolution of the theory of entrepreneurship. It was proved that the understanding of the content of the business potential is determined by the ability to create value proposition due to the presence of resources, capabilities and competencies. Adhering to the selected provisions of the dependence of the characteristic features of the entrepreneurial potential of the features of the development not only of the theory of entrepreneurship, but also of national economies, the prospects for further research are to identify the distinctive features inherent to entrepreneurs in terms of Ukrainian realities.
Entrepreneurial potential in the context of the evolution of the theory of entrepreneurship
Keywords: предпринимательство; предпринимательский потенциал; новаторская деятельность; предприниматель; entrepreneurship; entrepreneurial potential; innovative activities; entrepreneur